Pupillary dynamics predict long‐term outcome in a cohort of acute traumatic brain injury coma patients - Elena Monai; Chiara Favaretto; Anna Salvalaggio; Lorenzo Pini; Marina Munari; Maurizio Corbetta (Annals of Clinical and Translational Neurology, 2023)
Abstract Objective Examining the size and reactivity of the pupils of traumatic brain injury coma patients is fundamental in the Neuro‐intensive care unit (ICU). Pupil parameters on admission predict long‐term clinical outcomes. However, little is known about the dynamics of pupillary parameters and their potential value for outcome prediction. Methods This study applied a time‐course analysis of pupillary signals (size and photo‐reactivity) in acute traumatic brain injury coma patients (n = 20) to predict outcome at 6 months. Results The time course of pupillary signals was informative in discriminating favorable (F) versus unfavorable (U) outcomes, with the highest correlation within the 1st week notwithstanding pharmacological sedation. Patients with favorable outcome at 6 months showed more consistent in time isochoric and photo‐reactive pupils. In contrast, patients with an unfavorable outcome showed more variable measures that tended to stabilize toward pathological values. Interpretation Time‐dependent tracking of pupils' size and reactivity is a promising application for ICU monitoring and long‐term prognosis. These findings support the usefulness of automatic tools for the dynamic, quantitative, and objective measurements of pupils.